Global sliding mode observers for some uncertain nonlinear systems: dissipative approach - Apaza Pérez, Willy Alejandro (My University, 2018)
Sliding-mode observers, Velocity observers, Nonlinear observers, Dissipative observers
Keywords: Sliding-mode observers, Velocity observers, Nonlinear observers, Dissipative observers